Yawning and Stretching Predict Brain Temperature Changes in Rats: Support for the Thermoregulatory Hypothesis - Shoup-Knox, Melanie L.; Gallup, Andrew C.; Gallup, Gordon; McNay, Ewan C. (Frontiers in Evolutionary Neuroscience, 2010)
Recent research suggests that yawning is an adaptive behavior that functions to promote brain thermoregulation among homeotherms. To explore the relationship between brain temperature and yawning we implanted thermocoupled probes in the frontal cortex of rats to measure brain temperature before, during and after yawning. Temperature recordings indicate that yawns and stretches occurred during increases in brain temperature, with brain temperatures being restored to baseline following the execution of each of these behaviors. The circulatory changes that accompany yawning and stretching may explain some of the thermal similarities surrounding these events. These results suggest that yawning and stretching may serve to maintain brain thermal homeostasis.